Gynecologic Cancer InterGroup (GCIG) Consensus Review for Ovarian and Primary Peritoneal Low-Grade Serous Carcinomas. (1st November 2014) - Gourley, Charlie; Farley, John; Provencher, Diane M.; Pignata, Sandro; Mileshkin, Linda; Harter, Philipp; Maenpaa, Johanna; Kim, Jae-Weon; Pujaide-Lauraine, Eric; Glasspool, Rosalind M.; Ray-Coquard, Isabelle; Gershenson, David
Abstract : Abstract: Low-grade serous ovarian cancer is a recently described histological subtype of ovarian cancer that is clinically and molecularly distinct from the 4 other main histological subtypes (high-grade serous, clear cell, endometrioid, and mucinous). In particular, it differs from high-grade serous ovarian cancer in that it presents at a much younger age, is more indolent, and is relatively chemoresistant. Very few clinical trials have been performed exclusively in this tumor type; and as such, specific data guiding optimal management are limited.